Early short-term treatment with exogenous hydrogen sulfide postpones the transition from prehypertension to hypertension in spontaneously hypertensive rat. (2nd January 2018) - Tain, You-Lin; Hsu, Chien-Ning; Lu, Pei-Chen
ABSTACT: Hydrogen sulfide (H2 S), nitric oxide (NO), and renin–angiotensin system (RAS) are involved in hypertension. We examined whether early treatment with sodium hydrosulfide (NaHS), an exogenous H2 S donor, can regulate H2 S-generating pathway, NO pathway, and the RAS, to prevent the transition from prehypertension to hypertension in spontaneously hypertensive rats (SHRs). Four-week-old SHRs and control normotensive Wistar–Kyoto (WKY) rats were assigned into three groups: WKY, SHRs, and SHR + NaHS; SHRs were injected intraperitoneally with sodium hydrosulfide (14 μmol/kg/day) for 4 weeks. SHRs exhibited hypertension at 12 weeks of age, which was blocked by early sodium hydrosulfide administration. Concentrations of H2 S were increased in the kidney in SHR + NaHS group versus WKY. Sodium hydrosulfide reduces mRNA expression of four H2 S-generating enzymes and decreased 3-mercaptopyruvate sulphurtransferase protein level in SHRs. Early administration of sodium hydrosulfide decreases plasma N G monomethyl-l -arginine (l -NMMA, an inhibitor of NO synthase) level and increases plasma NO level in SHRs. Next, sodium hydrosulfide administration reduces renal mRNA expression of Ren, Atp6ap2, Agt, Ace, and Agtr1a in SHRs. We conclude that early short-term sodium hydrosulfide treatment increases renal H2 S concentrations, restores NO bioavailability, and blocks the RAS in the kidney, in favor of vasodilatation to prevent the development of hypertension in adult SHRs.